​​​The relationship between work life balance and mental workload in female nurses in the inpatient unit of Hospital X: A quantitative study - Utami, ​Indah Tri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
​​​Background: Mental workload in healthcare workers, especially female nurses, is a critical factor influencing job performance and well-being. Previous studies have suggested that work life balance significantly affects mental workload. This study aims to explore the relationship between work life balance and mental workload among female nurses in the inpatient unit of Hospital X. The findings could provide insights into how work-life balance interventions could reduce mental workload in healthcare settings. Methods: This quantitative study utilized a cross-sectional design, with data collected through questionnaires from 100 female nurses. The study employed chi-square tests to analyze the relationship between work life balance and mental workload, as well as logistic regression to identify dominant factors influencing mental workload. Statistical significance was determined at p < 0.05. Findings: The results revealed a significant relationship between work life balance and mental workload (p-value = 0.001). Nurses with higher education levels (S1 Ners) exhibited a stronger correlation with high mental workload (p-value = 0.018). The most dominant factor influencing mental workload was the education level (p-value = 0.004), with job satisfaction, employment status, and work experience serving as confounding variables. Conclusion: The study concludes that better work life balance, particularly through education, is crucial in mitigating mental workload in female nurses. Implementing work-life balance programs can improve the mental health and productivity of healthcare workers. Novelty/Originality of this article: This study contributes new insights into the relationship between work life balance and mental workload in the nursing profession, particularly in inpatient settings. It highlights the impact of education on mental workload, which has been less explored in previous studies.